Analysis of Mangrove Carbon Economic Potential and Community Based Mangrove Management in Mojo Village, Pemalang Regency - Delvita, Sisna; Penidda, Elbibiya Izzul; Nurjani, Emilya (Indonesian Society of Limnology, 2026)
Mangrove forests are vital for maintaining coastal ecosystem balance and mitigating climate change through blue carbon storage. This study present a novel integration of blue carbon economic valuation and community-Based mangrove Management (CBMM) assessment at the village scale, using mojo village, Indonesia as a case study. Mojo village was chosen as the research location because of the carbon potential that Mojo village has to be developed using the CBMM concept. A mixed-method approach combined secondary data analysis of mangrove carbon stocks with semi-structured interviews involving key members of the Pelita Bahari community group. The Mojo Village mangrove ecosystem demonstrated substantial blue carbon value, estimated between IDR 34.66 million and IDR 199.78 million per hectare under different carbon market scenarios, indicating substantial mitigation and financial potential. CBMM analysis reveals that strong local participation and institutional legitimacy support conservation outcomes; however, limited technical capacity, external dependence, and weak monitoring constrain readiness for carbon market participation. Analytically, the findings demonstrate that carbon valuation alone is insufficient without parallel governance strengthening. Community-based mangrove management supports the sustainability of coastal ecosystems and contributes to community welfare through the economic valorization of blue carbon. Beyond local benefits, this study contributes to the global blue carbon discourse by illustrating how village-level community management can inform scalable, socially inclusive pathways for integrating mangroves into national climate strategies, carbon markets, and international mitigation frameworks under the Paris Agreement.